Optimizing Concurrent Data Structures in Rust - Zhao, Xin (2025 5th International Conference on Consumer Electronics and Computer Engineering (ICCECE), 2025)
Lock- Free data structures are a key approach in concurrent programming that allows for thread-safe data manipulation without the need for traditional locking methods. They can diminish the overhead of context switching and lock contention in multi-threaded scenarios, which in turn boosts program performance. This paper investigates the efficient construction of lock-free concurrent data structures, harnessing Rust's type system and the commutativity of operations to attain a considerable performance enhancement compared to traditional atomic data types.